The natural economic science : re-writing economic fundamentals - Fudulu, Paul (Bingley, U.K. : Emerald Publishing Limited, 2019)
Economics is widely regarded as a social science. But the division of social vs. natural science limits the study of economics -- and, in fact, all social sciences -- locking away theories and evidence that greatly improve levels of analysis and research across all areas of interdisciplinary study. For too long now, this division has ceased to make sense. In this ground-breaking new study, Paul Fudulu bases a theory of new natural economic science on one of the most important causal laws of physics: the ever entropic degradation of the universe. This theory is comprehensive for all of human behavior, and makes it possible to find solutions to unsolved problems of orthodox economics, revealing correlations which are crucial to a solid economic analysis. Through a book of two parts, Fudulu takes readers through this new theory, starting at the basics and building to look at individual examples, including the formation of human ends and an exploration of coercive actions through the use of externalities as a cover-up. For students, researchers and academics in social sciences and economic theory, this is an unmissable book with an exciting new theory of natural economics.
Prelims -- Natural economic assumptions and methods -- Natural solutions to unsolvable problems of orthodox economics -- Endnotes -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Economics; Entropy; Business & Economics -- Economics -- Theory; Economics